The electroencephalogram in manic-depressive psychosis : relationship to psychological features and implications for a toxic-organic pathogenesis. - Hurst, Lewis Alfred (Department of Psychology, 2020)
This investigation was undertaken with a view in the first place to testing a claim of Pauline Davis as to the correlation, in manic-depressive psychosis, between certain psychological and electroencephalographic features, notably alpha frequency and irregular fast low voltage records which she termed "choppy". The scope undertaking is, however, wider in as much as we shall be testing correlations with rhythms other than the alpha, and not only in respect of frequency but also of amplitude and per cent time. Moreover the notion of "choppy" records will be subjected to critical analysis and replaced by a detailed characterization of irregular or organised records.